2018
DOI: 10.3390/f9090577
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Harvest Residues to Nutrient Cycling in a Tropical Acacia mangium Willd. Plantation

Abstract: Harvest residues can play a crucial role in conserving nutrients for recycling in forests, but little is known about the rates of decomposition and nutrient release from these residues following logging in tropical acacia plantations. In this study, we examined the biomass and nutrient content of harvest residue components (bark, leaves, and branches) using the litterbag technique for a 1.5-year-period following harvest of a seven-year-old Acacia mangium plantation in Northern Vietnam. At harvest, the total dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This finding fits well with the current plantation fertilization practice, which has demonstrated the benefits of P fertilization at time of planting [24,30]. Bich et al [37] emphasise the importance of P fertilization in Acacia plantations as it enhances microbial activity, decomposition rate, and microbial N fixation.…”
Section: Model Performancesupporting
confidence: 83%
“…This finding fits well with the current plantation fertilization practice, which has demonstrated the benefits of P fertilization at time of planting [24,30]. Bich et al [37] emphasise the importance of P fertilization in Acacia plantations as it enhances microbial activity, decomposition rate, and microbial N fixation.…”
Section: Model Performancesupporting
confidence: 83%
“…Uptake of K by age 4 y was 207 kg ha −1 ; harvest residue can contain 166-190 kg K ha −1 in A. mangium [4], and 102-115 kg K ha −1 in A. auriculiformis [32]. Bich et al [33] reported that Ca and K released from the harvest residue of A. mangium occurred very rapidly, and at a faster rate than other nutrients. Application of K fertiliser has increased the productivity of eucalypt plantations in Brazil [34] but in that case the soils were highly weathered and low in primary minerals [35] and with low exchangeable K < 8 mg kg −1 [36] compared to >40 mg kg −1 in South Sumatra.…”
Section: Response Of N K and Ca Fertilisersmentioning
confidence: 99%
“…The forest industry has been producing bioenergy through the combustion of residual materials (lignin/black liquor and woody residuals) to support their operations for nearly one century (Hannam et al, 2017) and wood wastes from harvesting, milling and manufacturing are increasingly being used as biomass fuel for bioenergy production (NRCan, 2020). Biomass removal on an industrial scale can contribute to the degradation of the site productivity over successive rotations (Van Bich et al, 2018) and result in increased soil acidity, which may negatively impact soil biodiversity (Jacobson et al, 2014; Reid & Watmough, 2014). Generally, the impact on nutrient removal and ecosystem function is proportional to the intensity of harvesting and the degree of biomass utilization (McFee & Kelly, 1995; Paré et al, 2002).…”
Section: Introductionmentioning
confidence: 99%